THE INFLUENCE OF PROFITABILITY, LIQUIDITY, AND DEBT TO THE DIVIDEND PAYOUT RATIO IN MANUFACTURING COMPANY (LISTED IN INDONESIAN STOCK EXCHANGE FROM 2008-2010) - Putri Kartika Sari; Sigit Handoyo (Jurnal Siasat Bisnis, 2015)
Abstract